Rice Self-Sufficiency and Optimization of Irrigation by Using System Dynamic - . Asmelita; Lily M. Limantara; M. Bisri; Widandi Soetopo; Indra Farni (Salehan Institute of Higher Education, 2024)
This research intends to optimize the results of irrigation canals with the conversion of function to fisheries without reducing rice self-sufficiency regionally. However, irrigation is an infrastructure asset that needs to be used optimally. It is due to the water; water sources and irrigation infrastructure can provide more benefits to rice fields, which are to function as fisheries in the study location (West Sumatra Province). The aim of this research is to propose the optimal combinations of irrigated land planted with rice and those in the form of fisheries. The methodology uses System Dynamics due to the official BPS data. There are many tools that are used in this system dynamics approach, such as causal diagrams, archetype systems, diagrams of stock and flow, and the behavior of over-time graphs. The DSS generator for simulating the program in this study uses Stella, which is a new paradigm in the water resources system approach. The result shows that the potential increase in income that could be obtained by converting the rice fields to tilapia fisheries is about 126 million Rupiah per year per hectare. West Sumatra Province, as a national rice granary, has many districts that are more self-sufficient in rice, so it can be considered to utilize irrigation to become the irrigation for fisheries. The potential of rice fields that can be converted into fisheries while maintaining self-sufficiency in rice at the district/city level of West Sumatra Province is more than 61 thousand hectares, and it generates an increase in income of about 7.7 trillion per year. Doi: 10.28991/CEJ-2024-010-02-010 Full Text: PDF